The Bloomsbury encyclopedia of design - Edwards, Clive, 1947- (London ; : Bloomsbury Academic, 2016)
"The Bloomsbury Encyclopedia of Design provides a comprehensive guide to design, with entries on key topics in the history and theory of design, addressing a range of design forms including graphic, textile, furniture, metal, ceramic, fashion, stage and film, vehicle and product design, as well as national histories of design and key design movements. The Encyclopedia provides up-to-date peer reviewed coverage of the last 250 years of design history, with global coverage by leading international design scholars and design historians. Complete with a comprehensive index and full cross referencing, The Bloomsbury Encyclopedia of Design is the definitive guide to Design"--
boek
Keywords: Design -- Encyclopedias; DESIGN / Reference; DESIGN / History & Criticism; REFERENCE / Encyclopedias